The massacre of civilians in the region of Švenčionys during the 19–20 May 1942 reprisal campaign for the killing of German officials by Soviet partisans. Part I - Zizas, Rimantas (Genocidas ir rezistencija, 2026)
The article seeks to shed light on the events of 19–20 May 1942 in the General District of Lithuania (Generalbezirk Litauen), in what were then the counties of Švenčionys and Svir: the provocative action carried out by Soviet partisans – the killing of German officials – and the retaliatory ‘reprisal campaign’ – the mass killing of civilians. This massacre was a traumatic event that complicated Lithuanian–Polish ethnic relations, as the victims of the reprisal campaign were predominantly Poles, and the Lithuanian police and officials from the Lithuanian self-government administration were involved in its execution. In Lithuanian historiography, this series of mass murders has received little detailed attention and remains largely unknown to the Lithuanian public. The history of the massacre has been studied primarily by Polish authors, but the narrative they present is politicised and contains a considerable number of propagandistic claims and various speculations. This article examines several contested issues and aspects of the massacre: its actual scale (the number of victims), the sites of the killings, the principal perpetrators, the principles (criteria) used in selecting victims for the reprisal campaign, the identity of the victims, and other related issues. With the collapse of the Blitzkrieg strategy, the reprisal campaign was carried out with the aim of deterring the population from resistance, intimidating them, and inducing psychological shock. In addition, the article puts forth the argument that the number of victims was actually lower than that claimed by the German occupation authorities and cited in Polish sources, and suggests that these figures were inflated and used for propaganda purposes.